Annual Report - Feinstein International Center (Tufts Archival Research Center, 2005)
The year 2006/7 has been one of consolidation for the Feinstein International Center after major changes were implemented in the preceding year. We hired new faculty and staff, reinforced existing research, and enhanced our teaching agenda. We attracted new funders to the Center and are playing a larger role in the academic life of Tufts University. Our research in Sudan and Uganda has expanded. Recruitment to our faculty of Dr. Andrew Wilder, formally director of the Afghan Research and Evaluation Unit (AREU), paves the way for further expanding the geographical scope of the Center's research in South and Central Asia. Our partnerships with African universities and research groups continue, as do those with western aid agencies. We have started a new partnership with Transparency International on a research program into the prevalence and effects of corruption in the humanitarian aid business. Throughout the year, Center faculty have been sought out by UN agencies, NGOs, and government aid departments to facilitate, chair, and advise upon the changing nature of humanitarian threats and response. In our educational agenda we continue to offer our Masters of Arts in Humanitarian Assistance degree and contribute to teaching in the Friedman School of Nutrition Science and Policy as well as the Fletcher School of Law and Diplomacy. Our joint Humanitarian Studies initiative with Harvard and MIT has undergone a major upgrade and the number of Ph.D. students supported by Center faculty continues to increase. Looking forward to 2007/8, we envisage the start of major long-term research initiatives examining the effects of repeated crises on vulnerable communities, the opportunities being offered by the spread of cell phone technology in Africa, and the increasingly complex relationship between security, economics, and humanitarian need across the world.